Estudo de caso de execução de aterros com misturas de argila e rejeito de bauxita - EÇA JUNIOR, José Roberto Guimarães (Universidade Federal do Pará, 2024)
The reuse of mining tailings is a real demand due to the search for sustainable exploitation of resources. Brazil is the holder of one of the largest mineral assets and, as such, is one of the largest producers and exporters of minerals on the planet. The search to meet the demand for the production and extraction of minerals has been growing every day and, along with this growth, the search for the reduction of environmental impact without loss of profitability has also been increasing. Currently, research with these objectives is extremely necessary in the search for solutions to these problems. Several studies seek alternatives for the reuse of the waste on a large scale, and one of the alternatives that make this application feasible are landfills within the enterprise itself. With the continuous updating of the regulations that govern dams, it is often necessary to reinforce old structures in order to increase the safety factor. This paper sought to analyze the applicability of mixing clay with bauxite tailings, in different proportions, for feasibility of its use in controlled landfills. In addition, it aimed to make feasible analyses regarding the research that evidenced the reuse of ore tailings and additions of other tailings materials. A case study was carried out in a mining company, collecting clay and tailings samples, and after being characterized, a pilot and an auxiliary mix were defined. As results, the mixture of 50% bauxite tailings with 50% clay resulted in a material that achieved California Support Index (CSI) values higher than those required by the Dnit 108 of 2009 standards, besides considerably improving the geomechanical characteristics when compared to the pure tailings. Thus, this research contributed to evaluate the applicability of compositions of clay and bauxite tailings in an experimental embankment in a mining area.